Interaction of subjects in the process of pre-professional pedagogical training of schoolchildren - Lyudmila V. Baiborodova (Saratov State University, 2023)
The research is relevant due to the fact that interaction of subjects is one of the most important conditions and mechanisms to improve the quality of pre-professional pedagogical training of schoolchildren. The aim of the study is twofold: to identify and characterize the opportunities for adults and children to interact that are not used in educational organizations; to determine the developmental directions and means of interaction between subjects. Hypothesis: teachers do not fully use the resource of subject interaction which is an important condition for improving the quality of pre-professional pedagogical training in psychological and pedagogical classes. Participants: a study was organized with the participation of teachers, children and parents from 7 regions of Russia (Kostroma region, Yaroslavl region, Arkhangelsk region, Republic of Karelia, Komi Republic, the city of Smolensk, the city of Petropavlovsk-Kamchatsky). The opinion of about 1000 respondents was studied to assess the level of interaction of subjects participating in pre-professional pedagogical training. Methods (tools): questionnaires were compiled based on the characteristics of the five components of interaction (mutual understanding, mutual recognition, relationships, mutual actions, mutual influence) developed by N. N. Obozov. The data of the research conducted earlier with the author's participation were also taken into account. Results: the research established that in general, the indicators of interaction between teachers and schoolchildren of psychological and pedagogical classes are slightly higher than in other classes, which is due to the general teachers and students' target settings. At the same time, in general, having established positive relationships, teachers adopt the position that slows down the formation of subjectivity in students. Conclusion: while organizing pre-professional pedagogical training, the resource of interaction between children and parents, teachers and parents, collaboration of schoolchildren of different ages, children and adult communities is not used enough. The findings should be taken into account to improve the effectiveness of psychological and pedagogical classes.